Increased expression of caspase 1 during active phase of connective tissue disease - Cai, Rentian; Wang, Qiongqiong; Zhu, Gongmin; Zhu, Liying; Tao, Zhen (PeerJ, 2019)
Key factors of pyroptosis play an important role in the inflammatory response to connective tissue disease (CTD). However, information on active and stable stages of CTD is scarce. To distinguish the differences of concentrations of C-reactive protein (CRP), caspase 1, caspase 4, caspase 5 and sCD14 in plasma between the patients with active and stable stages of CTD. A cohort study was conducted to recruit patients diagnosed with CTD of active phase and stable phase as well as health control. These data included the analysis of the concentration of sCD14, caspase 1, caspase 4 and caspase 5 in peripheral plasma by ELISA. The Wilcoxon rank-sum test was used to compare the two groups. The sex ratio and ages of the three groups were not different statistically. The concentrations of sCD14, caspase4 and caspase5 of plasma in the CTD of active phase and the stable phase as well as the health control. The concentration of caspase 1 in active phase of CTD (470.19 [422.33–513.14] pmol/L) was significantly higher than that in stable group (203.95 [160.94–236.12] pmol/L) and healthy control (201.65 [191.11–240.35] pmol/L] pmol/L) (p < 0.001, both), but there was no significant difference between stable group and healthy control (p = 0.2312). Similarly, the concentration of CRP in the active phase of CTD (8.96 [3.06–20.28] mg/L) was significantly higher than that in the stable group (3.00 [1.30–11.40] mg/L) and the healthy control (3.70 [2.30–4.73] mg/L) (p = 0.0013, p = 0.0006, respectively), but there was no significant difference between the stable group and the healthy control (p = 0.3205). However, there were no significant differences in the concentration of sCD14, caspase 4 and caspase 5 in the active phase of CTD and the stable group as well as the health group. Consequently, the patients of the active phase of CTD showed increased expression of caspase 1.
Keywords: Caspase 1; Caspase 4; Caspase 5; Connective tissue disease